Exploring Prosocial Behavior Among Students at Madrasah Aliyah Negeri Sidoarjo - Yarizky, Muhammad Alwy; Maryam, Effy Wardari (Indonesian Journal of Islamic Studies, 2024)
This study explores prosocial behavior among high school students, focusing on MAN Sidoarjo. Using a sample of 275 students, data was collected via a prosocial behavior scale and analyzed descriptively. Results indicate that while overall prosocial behavior is moderate, males exhibit lower levels compared to females. These findings emphasize the need to address gender differences in promoting prosocial behavior among high school students. Highlights : Gender differences: The study highlights a notable gender disparity in prosocial behavior among high school students. Descriptive analysis: Utilizing a quantitative approach, the research provides a detailed description of prosocial behavior patterns. Implications for intervention: Findings underscore the importance of addressing gender differences to promote prosocial behavior in educational settings. Keywords: Prosocial behavior, Gender disparity, High school students, Descriptive quantitative study, MAN Sidoarjo